Exploring the Biocultural Nexus of Gastrodia elata in Zhaotong: A Pathway to Ecological Conservation and Economic Growth - Yanxiao Fan; Menghua Tian; Defen Hu; Yong Xiong (Biology, 2025)
Gastrodia elata, known as Tianma in Chinese, is a valuable medicinal and nutritional resource. The favorable climate of Zhaotong City, Yunnan Province, China, facilitates its growth and nurtures rich biocultural diversity associated with Tianma in the region. Local people not only cultivate Tianma as a traditional crop but have also developed a series of traditional knowledge related to its cultivation, processing, medicinal use, and culinary applications. In this study, field surveys employing ethnobotanical methods were conducted in Yiliang County, Zhaotong City, from August 2020 to May 2024, focusing on Tianma. A total of 114 key informants participated in semi-structured interviews. The survey documented 23 species (and forms) from seven families related to Tianma cultivation. Among them, there were five Gastrodia resource taxa, including one original species, and four forms. These 23 species served as either target cultivated species, symbiotic fungi (promoting early-stage Gastrodia germination), or fungus-cultivating wood. The Fagaceae family, with 10 species, was the most dominant, as its dense, starch-rich wood decomposes slowly, providing Armillaria with a long-term, stable nutrient substrate. The cultural importance (CI) statistics revealed that Castanea mollissima, G. elata, G. elata f. flavida, G. elata f. glauca, G. elata f. viridis, and Xuehong Tianma (unknown form) exhibited relatively high CI values, indicating their crucial cultural significance and substantial value within the local community. In local communities, traditionally processed dried Tianma tubers are mainly used to treat cardiovascular diseases and also serve as a culinary ingredient, with its young shoots and tubers incorporated into dishes such as cold salads and stewed chicken. To protect the essential ecological conditions for Tianma, the local government has implemented forest conservation measures. The sustainable development of the Tianma industry has alleviated poverty, protected biodiversity, and promoted local economic growth. As a distinctive plateau specialty of Zhaotong, Tianma exemplifies how biocultural diversity contributes to ecosystem services and human well-being. This study underscores the importance of biocultural diversity in ecological conservation and the promotion of human welfare.